Comparison of Frequency Conversion Techniques for Magnetoelectric Sensors. (2015) - Salzer, S.; Höft, M.; Knöchel, R.; Hayes, P.; Yarar, E.; Piorra, A.; Quandt, E.
Abstract: Recent advances in magnetoelectric sensor systems prove their growing importance for biomagnetic sensing applications. But with increasing sensitivity down to some pT in mechanical resonance the sensors require techniques to convert low frequent biomagnetic signals in the range of 0.1 Hz to 40 Hz into the mechanical resonance frequency of the cantilevers to utilise the effect amplification of the first bending mode. This contribution introduces the frequency conversion via electrical modulation of the piezoelectric phase and readout via the piezoelectric phase in both basic theory and experiment and compares the results to a magnetic frequency conversion method. The electrical frequency conversion shifts the wanted signal into the mechanical resonance but, with the current setup and sensors, is about a decade less sensitive compared to the magnetic approach. ×Suitable offsets in the magnetic frequency conversion effectively reduce the noise level by more than two decades.